New routes for plant iron mining. Issue 2 (5th December 2016) - Curie, Catherine; Mari, Stéphane
Summary: Plant iron (Fe) uptake relies to a large extent on the capacity of cells to control and extract Fe pools safely conserved in extracytoplasmic environments such as the apoplast and vacuoles, at least as much as on the transport machinery nested in plasma membranes. Recent studies on root and embryo Fe nutrition support this assertion and show that the root Fe‐deficiency response also includes the dynamic use of a large Fe reservoir bound to cell wall components in the root apoplast, secretion in the apoplast of phenolic compounds of the coumarin family, which solubilize Fe in calcareous soils, and inhibition of suberization of endodermal cells in order to allow apoplastic and transcellular radial transport of Fe. All of these responses are regulated by the stress hormones ethylene and abscisic acid (ABA), suggesting an integrated strategy within the root to adapt to Fe shortage. For its nutrition, the embryo has developed both an original uptake mechanism, in which ascorbate is effluxed to chemically reduce Fe 3+ to the transport‐competent Fe 2+ form, and an efficient strategy to control utilization of a large Fe pool in vacuoles. This review will attempt to summarize exciting new insights into the diverse routes that Fe takes to feed plant tissues.   Contents     Summary 521 I. Introduction 521 II. How does the root extracellular space contribute to Fe nutrition? 522 III. Fe in the seed: acquisition and distribution strategies 523 IV. Conclusions and open questions 524   Acknowledgements 525   References 525